Occurrence of periodontal pathogens in ethnic groups from a native Brazilian reservation - Jardim Júnior, Elerson Gaetti [UNESP]; Pereira, Mauricio Fabiano [UNESP]; Vieira, Evanice Menezes Marçal [UNESP]; Schweitzer, Christiane Marie [UNESP]; Okamoto, Ana Cláudia [UNESP]; Ávila-Campos, Mario Julio (Elsevier B.V., 2015)
Objective: The present study was designed to evaluate the occurrence of periodontal pathogens in the subgingival biofilm of 100 native Brazilians living at the Umutina Indian Reservation, Mato Grosso State, Brazil.Methods: Periodontal clinical examinations were carried out prior to collection of subgingival biofilm, and the presence of 14 periodontal microorganisms was evaluated by polymerase chain reaction (PCR). The prevalence and risk analysis was performed using Cochran and Mantel-Haenszel statistics for dichotomous variables or Pearson's chi-squared test for analysis of proportions when variables had three or more categories. The interrelations between clinical and microbiological parameters were assessed using Fisher's exact test and the Mann-Whitney U test.Results: Individuals with chronic periodontitis were frequently colonized by the association between Porphyromonas gingivalis and Campylobacter rectus, P. gingivalis and Prevotella intermedia, or P. gingivalis and Tannerella forsythia. Patients with chronic periodontitis were also colonized by Porphyromonas gulae and P. intermedia or by the association between P. gulae and T. forsythia. P. gulae was detected only in the subgingival samples from natives on a traditional diet. Gingival bleeding was associated with Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, T. forsythia, P. gingivalis, P. gulae, Porphyromonas endodontalis, P. intermedia, and Prevotella nigrescens. Treponema denticola was uncommon.Conclusions: Peculiar microbiota was demonstrated to be associated with different periodontal disease statuses in native Brazilians, with modest occurrence of certain pathogens, such as T. denticola, and the presence of P. gulae in natives with gingivitis or chronic periodontitis.
Keywords: Gingivitis; Chronic periodontitis; Native Brazilians; Anaerobes